2016
DOI: 10.3389/fpsyg.2016.01651
|View full text |Cite
|
Sign up to set email alerts
|

Gender Agreement Attraction in Russian: Production and Comprehension Evidence

Abstract: Agreement attraction errors (such as the number error in the example “The key to the cabinets are rusty”) have been the object of many studies in the last 20 years. So far, almost all production experiments and all comprehension experiments looked at binary features (primarily at number in Germanic, Romance, and some other languages, in several cases at gender in Romance languages). Among other things, it was noted that both in production and in comprehension, attraction effects are much stronger for some feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 44 publications
9
49
0
Order By: Relevance
“…This issue need to be checked, especially if we consider that plural 3DO clitics used in the two studies are unmarked for gender in French ("les"), while they are marked in Italian ("li" and "le"). That gender is a potential intervener in agreement operations has been shown in a study with Slovak by Badecker and Kuminiak (2007) and in a study with Russian by Slioussar and Malko (2016). In Slovak and Russian, we find gender agreement between past tense verbs and the subject of the sentence, and, when there is a gender mismatch between the subject and a local modifier occurring between the verb and the subject, the past tense verb tends erroneously to agree in gender with the local modifier as shown in the Slovak and Russian examples below.…”
Section: Interference In Subject-verb Agreement and The Role Of A Wormentioning
confidence: 83%
“…This issue need to be checked, especially if we consider that plural 3DO clitics used in the two studies are unmarked for gender in French ("les"), while they are marked in Italian ("li" and "le"). That gender is a potential intervener in agreement operations has been shown in a study with Slovak by Badecker and Kuminiak (2007) and in a study with Russian by Slioussar and Malko (2016). In Slovak and Russian, we find gender agreement between past tense verbs and the subject of the sentence, and, when there is a gender mismatch between the subject and a local modifier occurring between the verb and the subject, the past tense verb tends erroneously to agree in gender with the local modifier as shown in the Slovak and Russian examples below.…”
Section: Interference In Subject-verb Agreement and The Role Of A Wormentioning
confidence: 83%
“…But whereas agreement errors have been widely studied in monolingual speakers 1 (Nicol, Forster, & Veres, 1997;Pearlmutter, Garnsey, & Bock, 1999;Acuña-Fariña, Meseguer, & Carreiras, 2014;Häussler, 2012;Tucker, Idrissi, & Almeida, 2015;Slioussar & Malko;Ristić, Molinaro, & Mancini, 2016), less is known about the comprehension of agreement in speakers whose native language differs from the societally dominant language, typically described as heritage speakers: bilingual speakers who are immigrants or children of immigrants and who were exposed to one language during childhood but then switched to the language of their host country (Scontras, Fuchs, & Polinsky, 2015). Here we use their agreement errors to examine whether number computations in a native language differ between monolingual and bilingual speakers, with the goal of better describing the mechanism that underlies the comprehension of agreement in the latter group.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of Experiment 2 was to test the model predictions for the linear and nonlinear cue combination rules using self‐paced reading for reflexive‐antecedent dependencies like those in Table . Importantly, many studies have shown that self‐paced reading measures reliably index retrieval operations during real‐time dependency formation (e.g., Chen et al., ; Dillon, Chow, & Xiang, ; Jäger, Benz, Roeser, Dillon, & Vasishth, ; Kush & Phillips, ; Paape, ; Parker, Lago, & Phillips, ; Slioussar & Malko, ; Tucker & Almeida, ; Tucker et al., ; Van Dyke & McElree, ; Wagers et al., 2009; Xiang, Grove, & Giannakidou, ). To this end, Experiment 2 fit the processing disruptions generated by the (mis)matching targets to the model predictions generated in Experiment 1 to determine which cue combination is used to guide retrieval for reflexive processing.…”
Section: Experiments 2: Testing the Model's Predictionsmentioning
confidence: 99%